Correlation between Efflux Pump Genes and Biofilm Formation with Antibiotic Resistance of Klebsiella pneumoniae - Ali, Mahaba R.; Ibrahim, Aida H. (Iraqi Journal of Science, 2025)
Background: Klebsiella pneumoniae is a common pathogen that causes nosocomial infections. The efflux pump, antibiotic resistance and the capacity to form biofilm are significant virulence factors of K. pneumoniae that play an essential role in infection persistence. The aim of this study was to determine the distribution of acrAB-tolC efflux pump genes and whether there is a link between these genes with antibiotic resistance and biofilm formation in K. pneumoniae isolated from various clinical sources. Methods: In total, 174 different clinical samples were collected from Baghdad hospitals. Based on morphological characteristics, culture media, and biochemical tests, only 97 were identified as K. pneumoniae. Diagnostic results were confirmed using the Vitek-2 system and molecular diagnosis by the 16SrRNA gene. The sensitivity of the isolates to fourteen antibiotics was tested. The ability of the most resistant isolates to produce biofilms was also examined. Efflux pump genes (acrA, acrB and tolC) were investigated by polymerase chain reaction (PCR). Results: All isolates (100%) were found to be resistant to ampicillin and amoxicillin-clavulanate. On the other hand, the resistance percentage to cefotaxime was 95.87%, while tigecycline had the lowest resistance rate of 11.43%. In addition, the ability of bacteria to produce biofilms varied as 63.07% were found to be strong, 29.23% were moderate, 7.69% were weak, and 23.52% were non-biofilm-producing. According to the findings, the percentages of acrA, acrB, and tolC in the genotype detection assay for efflux pump genes were 100%, 95.08%, and 85.1% respectively. Conclusion: A close connection was detected between efflux pumps, biofilm formation and antibiotic resistance.